Pelatihan Keterampilan Komunikasi Bahasa Asing (Inggris dan Mandarin) bagi SMK Negeri 1 Labuan Bajo untuk Meningkatkan Kualitas Pelayanan di Industri Perhotelan - Gracedelia Jeannywelasny Ngasa; Dewi Sartika Umul; Yohana Etheldreda Ine Dae; Yulianus Janur (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2024)
The hospitality industry is one of the main pillars in economic development, especially in tourist destinations that rely on tourist visits from various parts of the world. Communication skills are needed to be able to compete in the world of work in the tourism sector. This Community Service (PkM) aims to train foreign language communication skills (English and Mandarin) to improve the quality of service in the Hospitality Industry. The location of PkM is at SMK Negeri 1 Labuan Bajo. This Community Service (PkM) in its implementation uses a practical learning method. This practical learning method aims to provide students with a truly involved experience, so that they can gain a deeper understanding and skills that are relevant to practice in the field.